Effect of Preoperative Sagittal Balance on Cervical Laminoplasty Outcomes. Issue 21 (1st November 2016) - Oshima, Yasushi; Takeshita, Katsushi; Taniguchi, Yuki; Matsubayashi, Yoshitaka; Doi, Toru; Ohya, Junichi; Soma, Kazuhito; Kato, So; Oka, Hiroyuki; Chikuda, Hirotaka; Tanaka, Sakae
Abstract : Study Design: Retrospective case series. Objective: To clarify how preoperative global sagittal imbalance influences outcomes in patients with cervical compression myelopathy undergoing cervical laminoplasty. Summary of Background Data: The influence of sagittal balance on outcomes of cervical laminoplasty remains uncertain. Methods: The authors retrospectively reviewed data of 106 patients who underwent double-door cervical laminoplasty between 2004 and 2011 and investigated the influence of the C7 sagittal vertical axis (SVA) on outcome scores. Primary outcomes used were Japanese Orthopedic Association (JOA) scores, Numerical Rating Scale for neck or arm pain, the Short Form 36 Health Survey (physical and mental component summary scores ), and the Neck Disability Index (NDI). Results: Ninety-two patients with complete data were eligible for inclusion. The preoperative C7 SVA was ⩽5 cm in 64 patients (69.6%) and > 5 cm in 28 (30.4%). We compared each parameter by the magnitude of spinal sagittal balance (preoperative C7 SVA > 5 cm vs. C7 SVA ⩽ 5 cm) after adjusting for age via the least square mean analysis because the average age was significantly higher in patients with C7 SVA > 5 cm. As for the radiographic parameters, both C2–7 SVA and C7 SVA were larger in patients when the C7 SVA was > 5 cm. Numerical Rating Scale for postoperative arm pain, postoperative JOA scores, and both pre- and postoperative physical component summary and NDI were worse in patients with C7 SVA > 5 cm; however, the JOA score recovery rate and changes in physical component summary and NDI were not significantly different. Conclusion: Postoperative functional outcome scores were significantly lower in patients with C7 SVA > 5 cm, although the improvement after cervical laminoplasty was not greatly affected. The involvement of global sagittal balance and cervical regional alignment should be considered in evaluating surgical outcomes for patients undergoing cervical laminoplasty. Level of Evidence: 4